Small mammals as sentinels of antimicrobial-resistant staphylococci - Kmeť, Vladimír; Čuvalová, Anna; Stanko, Michal (Folia microbiologica, 2018)
A total of 39 coagulase-negative staphylococci and seven Staphylococcus aureus strains were isolated from small mammal feces, i.e., the striped field mouse (Apodemus agrarius) and the yellow-necked mouse (A. flavicollis) in two sampling areas, deciduous forest and karst plains. MALDI-TOF analysis revealed five species of coagulase-negative staphylococci: S. sciuri, S. hominis, S. warneri, S. haemolyticus, and S. xylosus. All strains were susceptible to tetracycline, linezolid, vancomycin, and teicoplanin. Three MRSA strains with the mecA gene were detected. The beta-lactamase gene blaZ was detected in ampicillin-resistant staphylococci and in the high-level resistant strains (oxacillin over 2 mg/L) mecA gene. The mecC gene was not detected by PCR. Erythromycin-resistant staphylococci harbored the ermC gene and/or the efflux gene msrA. There were no detectable dfr genes in trimethoprim-resistant staphylococci and the rifampicin-resistant strains were without mutation in the rpoB gene. In summary, wild small mammals may serve as sentinels of mecA-positive S. aureus with erythromycin resistance genes ermC and efflux msrA. Small mammals appear to be useful indicators of antibiotic resistance.
Keywords: Methicillin-Resistant Staphylococcus aureus; Animals, Wild; Anti-Bacterial Agents; bakteriální léková rezistence; Drug Resistance, Bacterial; Coagulase; Microbial Viability; mikrobiální viabilita; Staphylococcal Infections; koagulasa; stafylokokové infekce; Microbial Sensitivity Tests; divoká zvířata; Rodentia; zvířata; hlodavci; antibakteriální látky; methicilin rezistentní Staphylococcus aureus; mikrobiální testy citlivosti; Staphylococcus; Animals